2010
DOI: 10.3758/s13428-010-0018-z
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive norms for 245 Italian idiomatic expressions

Abstract: The present study reports descriptive normative measures for 245 Italian verbal idiomatic expressions. For each of the idiomatic expressions the following variables are reported: Length, Knowledge, Familiarity, Age of Acquisition, Predictability, Syntactic flexibility, Literality and Compositionality. Syntactic flexibility was assessed using five syntactic operations: adverb insertion, adjective insertion, left dislocation, passive and movement. The psycholinguistic relevance of each dimension, their measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
101
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(113 citation statements)
references
References 74 publications
9
101
3
Order By: Relevance
“…According to Conner et al, in the same way as for single words, older adults experience retrieval difficulty with idioms. A potential weakness of the procedure used by Tabossi et al (2011) is that, since it is a somewhat difficult and time-consuming task, the possibility cannot be excluded that certain participants may have answered that they did not know the definition of an idiom to avoid having to produce a definition. However, in Tabossi et al's (2011) study, this phenomenon did not occur, as the reliable correlation found between familiarity and knowledge (.49) suggests.…”
Section: Theoretical Issues Addressed In the Processing Of Idiomatic mentioning
confidence: 99%
See 4 more Smart Citations
“…According to Conner et al, in the same way as for single words, older adults experience retrieval difficulty with idioms. A potential weakness of the procedure used by Tabossi et al (2011) is that, since it is a somewhat difficult and time-consuming task, the possibility cannot be excluded that certain participants may have answered that they did not know the definition of an idiom to avoid having to produce a definition. However, in Tabossi et al's (2011) study, this phenomenon did not occur, as the reliable correlation found between familiarity and knowledge (.49) suggests.…”
Section: Theoretical Issues Addressed In the Processing Of Idiomatic mentioning
confidence: 99%
“…Tabossi et al (2011) used this original procedure in Italian participants. They had to explain the meaning of each idiom they knew, but not if they were unfamiliar with an item.…”
Section: Theoretical Issues Addressed In the Processing Of Idiomatic mentioning
confidence: 99%
See 3 more Smart Citations